Method for preparing metal-organic framework structure material from PET waste fabric
Through alkali metal hydroxide hydrolysis and metal salt blending reaction, the degradation and dye removal problems of colored PET waste fabrics were solved, and high-purity metal-organic frame materials were prepared, achieving efficient recycling and reuse of PET waste fabrics. It has the advantages of green environmental protection and economic benefits.
Patent Information
- Application Number
- CN202411426631.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2024-12-31
AI Technical Summary
The prior art is difficult to efficiently degrade and recycle colored PET waste fabrics containing different dyes, and the existing dye removal methods are economical and unpractical, resulting in PET textiles being usually landfilled or incinerated after their service life, posing an ecological threat.
Alkaline metal hydroxide hydrolyzed polyethylene terephthalate waste fabric to produce terephthalic acid, and then adjusted pH value and decolorized multiple times, and finally blended with metal salt to prepare high-purity metal -Organic frame structure material.
It realizes efficient decomposition and decolorization of PET waste fabrics, and generates high-purity metal-organic frame materials, which are green and environmentally friendly, low cost and high yields. It is suitable for gas adsorption, catalysis, energy storage and other applications, and provides complex color PET waste materials. Recycling and upgrade solutions.
Smart Images

Figure CN119219935A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyethylene terephthalate waste fabric degradation, and in particular relates to a method for preparing a metal-organic framework structure material by using polyethylene terephthalate waste fabric. Background Art
[0002] Polyethylene terephthalate (PET) is a semi-aromatic polyester widely used in fiber manufacturing and textile industry due to its excellent physical, thermal, optical and mechanical properties. Nearly 70 million PET are produced worldwide each year. Due to the large consumption of non-renewable petroleum in the production process of PET and its difficulty in biodegradation, PET waste poses a serious threat to the global ecosystem. According to statistics, more than 60% of PET is used for synthetic fibers and textile products, while bottle-grade PET accounts for only 30%. In theory, fiber-grade PET is more suitable for chemical recycling than bottle-grade PET (0.95 dL / g) due to its lower intrinsic viscosity (0.4–0.75 dL / g).
[0003] However, most current chemical recycling attempts target clean, high-purity, non-pigmented bottle-grade PET. Few studies have used colored PET fabrics containing different dyes for degradation. On the other hand, mechanical recycling of complex PET waste requires effective sorting, separation and cleaning, which is less economical. In addition, colors and additives accelerate the quality loss of the final product during the recycling process, leading to product degradation. Therefore, most complex PET textiles are usually landfilled or incinerated at the end of their service life.
[0004] From a sustainable development perspective, dye decolorization is one of the biggest bottlenecks in the recycling and upcycling of colored PET textiles. Existing dye removal methods in PET recycling processes mainly include: 1) decolorization of PET fabrics before recycling, and 2) decolorization of monomers or liquids after decomposition. These two methods may be effective in laboratory-scale tests, but from an economic perspective, they are neither efficient nor practical due to the extended time and cost required, and the procedures are cumbersome. Therefore, there are few studies on the recycling of colored PET waste, and most of them focus on downcycling applications or the preparation of chemical degradation catalysts.
[0005] Hydrolytic recycling is considered a promising approach to treat complex PET wastes, which is highly tolerant to additives and colorants in aqueous solutions. Hydrolysis with bases as reactants has received particular attention due to its low cost, ease of operation, and the fact that the main product is terephthalic acid (TPA). The produced TPA, as the most widely used semiaromatic monomer, can become a chemical building block for other value-added products, including catalysts, metal-organic frameworks (MOFs), and biodegradable plastics, as well as regenerating PET through polymerization.
[0006] As a class of crystalline materials composed of metal clusters / ions and organic ligands, MOFs have high specific surface area, designable composition and adjustable pore size, and therefore have been widely studied for applications such as gas adsorption and separation, chemical sensing, catalysis, energy storage and conversion, etc. Considering that most of the current high-purity and pigment-free bottle-grade PET is used as a polymer ligand to synthesize TPA-based MOF materials, it is obvious that upgrading PET waste fabrics into MOFs will be of great significance from both economic and environmental perspectives. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide a method for preparing a metal-organic framework material using waste polyethylene terephthalate fabric in view of the deficiencies of the above-mentioned prior art. The method can efficiently generate MOF while achieving the decomposition and decolorization of colored PET, and has the advantages of being green, environmentally friendly, sustainable development, low cost and high yield.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a metal-organic framework material using waste polyethylene terephthalate fabric, the method comprising:
[0009] S1. Add polyethylene terephthalate waste fabric to an alkali metal hydroxide aqueous solution with a concentration of 0.25 mol / -2.5 mol / L, mix well, heat from room temperature to 120° C. at a heating rate of 5° C. / min, perform hydrolysis reaction at a constant temperature for 120 min, and naturally cool to room temperature to obtain an intermediate product;
[0010] S2, adding sulfuric acid solution to the intermediate product obtained in S1 to adjust the pH value to 3-4 to obtain a mixed solution, centrifuging, collecting the precipitate, washing and decolorizing with ethanol, and vacuum drying to obtain terephthalic acid as a white solid;
[0011] S3. Dissolve the terephthalic acid and metal salt obtained in S2 in a solvent, stir and mix evenly, react in a reactor at a temperature of 140° C. to 210° C. for 6 h to 24 h, cool naturally to room temperature, centrifuge, wash the precipitate with ethanol, and vacuum dry to obtain a metal-organic framework material; the solvent is one or more of N,N-dimethylformamide, water and formic acid.
[0012] Preferably, the alkali metal hydroxide in the alkali metal hydroxide aqueous solution in S1 is LiOH, NaOH or KOH.
[0013] Preferably, the vacuum drying in S2 is carried out at a temperature of 80° C. and for 12 hours.
[0014] Preferably, the metal salt in S3 is an aluminum salt, an iron salt, a zirconium salt, a chromium salt, a cobalt salt or a nickel salt.
[0015] Preferably, the molar ratio of terephthalic acid and metal salt in S3 is (0.96-1):1.
[0016] Preferably, the vacuum drying in S3 is carried out at a temperature of 90° C. to 100° C. and for a time of 8 h to 24 h.
[0017] The metal-organic framework structure material prepared by the present invention is used in environmental restoration such as gas adsorption and separation, catalyst carrier, energy storage material, drug delivery and sewage treatment.
[0018] Compared with the prior art, the present invention has the following advantages:
[0019] 1. The present invention realizes the efficient recovery and reuse of waste polyethylene terephthalate resources and prepares high-value MOF materials. Polyethylene terephthalate (PET) is degraded by alkali metal hydroxide to generate terephthalate and ethylene glycol, and then the dye is removed by adjusting the pH and washing multiple times to obtain high-purity terephthalic acid. Finally, it is blended with a metal salt solution to generate a well-crystallized MOF material.
[0020] 2. The whole process of the present invention is green, simple, efficient and sustainable. The terephthalic acid obtained in the hydrolysis process is effectively decolorized, and then chemically coordinated with the metal salt in the solution to generate a high-purity and well-crystallized MOF material. The washing and decolorization steps are simple and will not reduce the yield, which is conducive to the generation of nano MOF materials.
[0021] 3. The present invention does not use a large amount of organic solvents, thus reducing the reaction cost. The terephthalic acid is prepared by alkaline hydrolysis and then mixed with a metal salt solution for reaction. The preparation process is simple and the reaction process is controllable, which is suitable for large-scale treatment of waste PET.
[0022] 4. The present invention has low-cost raw materials, no need for catalysts, simple operation, and low equipment requirements. It is a green, efficient, simple, and sustainable method for preparing MOF materials, and has great potential for practical application. The method provides a basis for the recycling and upgrading of industrial-grade complex colored PET waste, has significant economic and social effects for the large-scale recycling and reuse of urban and industrial waste polyester, and provides a new idea for the large-scale preparation of MOF materials.
[0023] The present invention is further described in detail below with reference to the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The scanning electron microscope image, physical image and X-ray diffraction spectrum of the Al-MOF material prepared in Example 1 of the present invention.
[0025] Figure 2 The scanning electron microscope image, physical image and X-ray diffraction spectrum of the Fe-MOF material prepared in Example 2 of the present invention.
[0026] Figure 3 The scanning electron microscope image, physical image and X-ray diffraction spectrum of the Zr-MOF material prepared in Example 3 of the present invention.
[0027] Figure 4 The scanning electron microscope image, physical image and X-ray diffraction spectrum of the Cr-MOF material prepared in Example 4 of the present invention.
[0028] Figure 5 The scanning electron microscope image, physical image and X-ray diffraction spectrum of the Co-MOF material prepared in Example 5 of the present invention.
[0029] Figure 6 The scanning electron microscope image, physical image and X-ray diffraction spectrum of the Ni-MOF material prepared in Example 6 of the present invention. DETAILED DESCRIPTION
[0030] Example 1
[0031] The method for preparing a metal-organic framework material using polyethylene terephthalate waste fabric in this embodiment is as follows:
[0032] S1. Add 1.0 g of polyethylene terephthalate waste fabric to 100 mL of 2 mol / L NaOH aqueous solution, mix well, heat from room temperature to 120° C. at a heating rate of 5° C. / min, perform hydrolysis reaction at constant temperature for 120 min, cool naturally to room temperature, and obtain an intermediate product, i.e., disodium terephthalate and ethylene glycol aqueous solution;
[0033] S2, adding sulfuric acid solution to the intermediate product obtained in S1 to adjust the pH value to 3, to obtain a mixed solution, centrifuging, collecting the precipitate, washing and decolorizing with ethanol 3 times, and vacuum drying at 80° C. for 12 h to obtain terephthalic acid (TPA), a white solid;
[0034] S3. Dissolve 5 mmol (0.83 g) of terephthalic acid obtained in S2 and 5 mmol (1.876 g) of aluminum nitrate nonahydrate in 30 mL of N,N-dimethylformamide, stir and mix evenly, react in a reactor at a temperature of 150°C for 18 hours, cool naturally to room temperature, and obtain a suspension containing a crude Al-MOF product. Centrifuge at 8000 r / min, wash the precipitate with ethanol 3 times, remove residual raw materials and DMF, and vacuum dry at 100°C for 24 hours to obtain a metal-organic framework material, i.e., Al-MOF material.
[0035] Figure 1 a and b are scanning electron microscope images of Al-MOF materials. Figure 1 The c in the figure is a physical picture of Al-MOF material. Figure 1 d in the figure is the X-ray diffraction spectrum of Al-MOF material. From the scanning electron microscope image, it can be seen that the morphology of Al-MOF material is relatively regular, with a rod-like structure and a size of 1μm to 3μm. From the X-ray powder diffraction spectrum, it can be seen that Al-MOF material has significant characteristic diffraction peaks, indicating the successful synthesis of Al-MOF material.
[0036] The metal-organic framework material prepared in this embodiment can be used as a catalyst or catalyst carrier due to its unique pore structure and stability, and is particularly suitable for oxidation reactions, photocatalysis and other fields.
[0037] Example 2
[0038] The method for preparing a metal-organic framework material using polyethylene terephthalate waste fabric in this embodiment is as follows:
[0039] S1. Add 1.0 g of polyethylene terephthalate waste fabric to 100 mL of 2.5 mol / L KOH aqueous solution, mix well, heat from room temperature to 120° C. at a heating rate of 5° C. / min, perform hydrolysis reaction at constant temperature for 120 min, cool naturally to room temperature, and obtain an intermediate product, namely, dipotassium terephthalate and ethylene glycol aqueous solution;
[0040] S2, adding sulfuric acid solution to the intermediate product obtained in S1 to adjust the pH value to 4 to obtain a mixed solution, centrifuging, collecting the precipitate, washing and decolorizing with ethanol 4 times, and vacuum drying at 80° C. for 12 h to obtain terephthalic acid as a white solid;
[0041] S3. Dissolve 5 mmol (0.83 g) of terephthalic acid obtained in S2 and 5 mmol (1.35 g) of ferric chloride hexahydrate in 30 mL of N,N-dimethylformamide, stir and mix evenly, react in a reactor at a temperature of 160°C for 12 hours, and naturally cool to room temperature to obtain a suspension containing a crude Fe-MOF product. Centrifuge at 8000 r / min, wash the precipitate with ethanol 3 times, remove the residual raw materials and DMF, and vacuum dry at 100°C for 24 hours to obtain a metal-organic framework material, namely, Fe-MOF material.
[0042] Figure 2 a and b are scanning electron microscope images of Fe-MOF materials. Figure 2 The c in the figure is a physical picture of Fe MOF material. Figure 2d in the figure is the X-ray diffraction spectrum of the Fe-MOF material. From the scanning electron microscope image, it can be seen that the morphology of the Fe-MOF material is relatively regular, similar to a block structure, with a size of 1μm to 6μm. From the X-ray powder diffraction spectrum, it can be seen that the Fe-MOF material has a significant characteristic diffraction peak, indicating the successful synthesis of the Fe-MOF material.
[0043] The metal-organic framework material prepared in this embodiment has a simple preparation process, and the iron element in the metal coordination center is widely available, cheap, easily available, and green and environmentally friendly, which improves its application applicability in the field of pollution control of difficult-to-degrade industrial wastewater such as printing and dyeing.
[0044] Example 3
[0045] The method for preparing a metal-organic framework material using polyethylene terephthalate waste fabric in this embodiment is as follows:
[0046] S1. Add 1.0 g of polyethylene terephthalate waste fabric to 100 mL of 0.25 mol / L KOH aqueous solution, mix well, heat from room temperature to 120° C. at a heating rate of 5° C. / min, perform hydrolysis reaction at constant temperature for 120 min, cool naturally to room temperature, and obtain an intermediate product, namely, dilithium terephthalate and ethylene glycol aqueous solution;
[0047] S2, adding sulfuric acid solution to the intermediate product obtained in S1 to adjust the pH value to 4 to obtain a mixed solution, centrifuging, collecting the precipitate, washing and decolorizing with ethanol 4 times, and vacuum drying at 80° C. for 12 h to obtain terephthalic acid as a white solid;
[0048] S3. Dissolve 4.8mmol (0.8g) of terephthalic acid obtained in S2 and 5mmol (1.6g) of zirconium oxychloride octahydrate in 30mL of N,N-dimethylformamide, then add 15mL (397.5mmol) of formic acid, stir and mix evenly, react in a reactor at a temperature of 140°C for 6h, cool naturally to room temperature, and obtain a suspension containing a crude Zr-MOF product. Centrifuge at 8000r / min, wash the precipitate with ethanol 3 times, and vacuum dry at 100°C for 24h to obtain a metal-organic framework material, i.e., Zr-MOF material.
[0049] Figure 3 a and b are scanning electron microscope images of Zr-MOF materials. Figure 3 The c in the figure is a physical picture of Zr-MOF material. Figure 3d in the figure is the X-ray diffraction spectrum of the Zr-MOF material. From the scanning electron microscope image, it can be seen that the morphology of the Zr-MOF material is relatively regular and is a nanoparticle with a size of 500nm to 800nm. From the X-ray powder diffraction spectrum, it can be seen that the Zr-MOF material has a significant characteristic diffraction peak, indicating the successful synthesis of the Zr-MOF material.
[0050] The metal-organic framework material prepared in this embodiment provides a new opportunity for preparing high-performance Zr-MOF, which can promote the development of next-generation supercapacitors and environmental remediation.
[0051] Example 4
[0052] The method for preparing a metal-organic framework material using polyethylene terephthalate waste fabric in this embodiment is as follows:
[0053] S1. Add 1.0 g of polyethylene terephthalate waste fabric to 100 mL of 2 mol / L NaOH aqueous solution, mix well, heat from room temperature to 120° C. at a heating rate of 5° C. / min, perform hydrolysis reaction at constant temperature for 120 min, cool naturally to room temperature, and obtain an intermediate product, i.e., disodium terephthalate and ethylene glycol aqueous solution;
[0054] S2, adding sulfuric acid solution to the intermediate product obtained in S1 to adjust the pH value to 4 to obtain a mixed solution, centrifuging, collecting the precipitate, washing and decolorizing with ethanol 4 times, and vacuum drying at 80° C. for 12 h to obtain terephthalic acid as a white solid;
[0055] S3, 5mmol (0.83g) of terephthalic acid obtained in S2 and 5mmol (1.33g) of chromium trichloride hexahydrate were dissolved in 2.78mol (50mL) of deionized water, stirred and mixed evenly, reacted in a reactor at a temperature of 210°C for 8h, and naturally cooled to room temperature to obtain a suspension containing a crude Cr-MOF product. The suspension was centrifuged at 8000r / min, and the precipitate was washed with ethanol 3 times. After vacuum drying at 100°C for 24h, a metal-organic framework material, i.e., Cr-MOF material, was obtained.
[0056] Figure 4 a and b are scanning electron microscope images of Cr MOF materials. Figure 4 The c in the figure is a physical picture of Cr-MOF material. Figure 4 d in the figure is the X-ray diffraction spectrum of Cr-MOF material. From the scanning electron microscope image, it can be seen that the morphology of Cr-MOF material is relatively regular, with a triangular pyramid structure and a size of 200nm to 400nm. From the X-ray powder diffraction spectrum, it can be seen that Cr-MOF material has significant characteristic diffraction peaks, indicating the successful synthesis of Cr-MOF material.
[0057] The metal-organic framework material prepared in this example has significant advantages in hydrogen storage applications and shows great economic potential.
[0058] Example 5
[0059] The method for preparing a metal-organic framework material using polyethylene terephthalate waste fabric in this embodiment is as follows:
[0060] S1. Add 2.5 g of polyethylene terephthalate waste fabric to 100 mL of 2 mol / L NaOH aqueous solution, mix well, heat from room temperature to 120° C. at a heating rate of 5° C. / min, perform hydrolysis reaction at constant temperature for 120 min, cool naturally to room temperature, and obtain an intermediate product, i.e., disodium terephthalate and ethylene glycol aqueous solution;
[0061] S2, adding sulfuric acid solution to the intermediate product obtained in S1 to adjust the pH value to 3 to obtain a mixed solution, centrifuging, collecting the precipitate, washing and decolorizing with ethanol 3 times, and vacuum drying at 80° C. for 12 h to obtain terephthalic acid as a white solid;
[0062] S3, 12mmol (2.047g) of terephthalic acid obtained in S2 and 12mmol (3.50g) of cobalt nitrate hexahydrate were dissolved in 30mL N,N-dimethylformamide and 15mL deionized water, stirred and mixed evenly, reacted in a reactor at a temperature of 180°C for 24h, and naturally cooled to room temperature to obtain a suspension containing a crude Co-MOF product. The suspension was centrifuged at 8000r / min, and the precipitate was washed 3 times with ethanol. After vacuum drying at 90°C for 8h, a metal-organic framework material, i.e., Co-MOF material, was obtained.
[0063] Figure 5 a and b are scanning electron microscope images of Co-MOF materials. Figure 5 The c in the figure is a physical picture of Co-MOF material. Figure 5 d in the figure is the X-ray diffraction spectrum of the Co-MOF material. From the scanning electron microscope image, it can be seen that the morphology of the Co-MOF material is relatively regular, similar to a block structure, with a size of 2μm to 5μm. From the X-ray powder diffraction spectrum, it can be seen that the Co-MOF material has a significant characteristic diffraction peak, indicating the successful synthesis of the Co-MOF material.
[0064] The metal-organic framework material prepared in this embodiment has wide applications in catalysis, gas adsorption and separation, and electrochemical energy storage. The preparation process of this embodiment prepares Co-MOF by a green and low-cost method, further improving its economic feasibility in energy storage and environmental governance.
[0065] Example 6
[0066] The method for preparing a metal-organic framework material using polyethylene terephthalate waste fabric in this embodiment is as follows:
[0067] S1. Add 2.5 g of polyethylene terephthalate waste fabric to 100 mL of 2 mol / L NaOH aqueous solution, mix well, heat from room temperature to 120° C. at a heating rate of 5° C. / min, perform hydrolysis reaction at constant temperature for 120 min, cool naturally to room temperature, and obtain an intermediate product, i.e., disodium terephthalate and ethylene glycol aqueous solution;
[0068] S2, adding sulfuric acid solution to the intermediate product obtained in S1 to adjust the pH value to 3 to obtain a mixed solution, centrifuging, collecting the precipitate, washing and decolorizing with ethanol 3 times, and vacuum drying at 80° C. for 12 h to obtain terephthalic acid as a white solid;
[0069] S3, 12mmol (2.047g) of terephthalic acid obtained in S2 and 12mmol (3.4g) of nickel nitrate hexahydrate were dissolved in 30mL N,N-dimethylformamide and 15mL deionized water, stirred and mixed evenly, reacted in a reactor at a temperature of 180°C for 24h, and naturally cooled to room temperature to obtain a suspension containing a crude Ni-MOF product. The suspension was centrifuged at 8000r / min, and the precipitate was washed with ethanol 3 times. After vacuum drying at 90°C for 8h, a metal-organic framework material, i.e., Ni-MOF material, was obtained.
[0070] Figure 6 a and b are scanning electron microscope images of Ni-MOF materials. Figure 6 The c in the figure is a physical picture of Ni-MOF material. Figure 6 d in the figure is the X-ray diffraction spectrum of Ni-MOF material. From the scanning electron microscope image, it can be seen that the morphology of Ni-MOF material is relatively regular, with a rod-like structure and a size of 500nm to 3μm. From the X-ray powder diffraction spectrum, it can be seen that Ni-MOF material has significant characteristic diffraction peaks, indicating the successful synthesis of Ni-MOF material.
[0071] The metal-organic framework structure material prepared in this embodiment is used in the fields of electrocatalytic hydrogen production and gas adsorption and separation, especially in the fields of energy storage and environmental governance. It has significant economic and environmental value while improving efficiency and reducing costs.
[0072] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a metal-organic framework material using waste polyethylene terephthalate fabric, characterized in that: The method is: S1. Add polyethylene terephthalate waste fabric to an alkali metal hydroxide aqueous solution with a concentration of 0.25 mol / -2.5 mol / L, mix well, heat from room temperature to 120° C. at a heating rate of 5° C. / min, perform hydrolysis reaction at a constant temperature for 120 min, and naturally cool to room temperature to obtain an intermediate product; S2, adding sulfuric acid solution to the intermediate product obtained in S1 to adjust the pH value to 3-4 to obtain a mixed solution, centrifuging, collecting the precipitate, washing and decolorizing with ethanol, and vacuum drying to obtain terephthalic acid as a white solid; S3. Dissolve the terephthalic acid and metal salt obtained in S2 in a solvent, stir and mix evenly, react in a reactor at a temperature of 140° C. to 210° C. for 6 h to 24 h, cool naturally to room temperature, centrifuge, wash the precipitate with ethanol, and vacuum dry to obtain a metal-organic framework material; the solvent is one or more of N,N-dimethylformamide, water and formic acid.
2. The method for preparing a metal-organic framework material using waste polyethylene terephthalate fabric according to claim 1, characterized in that: The alkali metal hydroxide in the alkali metal hydroxide aqueous solution in S1 is LiOH, NaOH or KOH.
3. The method for preparing a metal-organic framework material using waste polyethylene terephthalate fabric according to claim 1, characterized in that: The vacuum drying in S2 is carried out at a temperature of 80° C. and for a time of 12 h.
4. The method for preparing a metal-organic framework material using waste polyethylene terephthalate fabric according to claim 1, characterized in that: The metal salt in S3 is aluminum salt, iron salt, zirconium salt, chromium salt, cobalt salt or nickel salt.
5. The method for preparing a metal-organic framework material using waste polyethylene terephthalate fabric according to claim 1, characterized in that: The molar ratio of terephthalic acid and metal salt in S3 is (0.96-1):
1.
6. The method for preparing a metal-organic framework material using waste polyethylene terephthalate fabric according to claim 1, characterized in that: The vacuum drying in S3 is carried out at a temperature of 90° C. to 100° C. and for a time of 8 h to 24 h.
Citation Information
Cited By
Preparation method and application of MOF (Metal Organic Framework) catalyst taking PET (Polyethylene Terephthalate) waste plastics as ligand source
CN119955117A